Perbandingan Relasi Gender Novel “Maransi” Karya A.R. Rizal dan Novel “Re: dan Perempuan” Karya Maman Suherman - Nola Florina (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2024)
This article aims to describe the results of women's gender analysis and the differences in views of A.R. Rizal and Maman Suherman regarding gender relations in their novels. This article uses a qualitative descriptive method. The object of this research is the novels "Maransi" and "Re and Perempuan". This article focuses on problems related to women's injustice and women's consciousness which are studied using gender analysis. Data was obtained using reading and note-taking techniques. The results of this research show: (1) the novel "Maransi" presents gender relations which are dominated by men. A slight difference with the novel "Re: and Perempuan" where the beginning of the story also presents male domination, but continues with the character's efforts to fight against male domination. In the end, the characters in the novel "Re: and Perempuan" prove that women are not always under the power of men. (2) The novel "Maransi" presents a story about the strong culture that influences freedom for women. The novel "Re and Perempuan" presents resistance to male domination, thus proving that women can be independent and powerful.